Herpes zoster correlates with increased risk of Parkinson's disease in older people: A population-based cohort study in Taiwan. Issue 7 (February 2017) - Lai, Shih-Wei; Lin, Chih-Hsueh; Lin, Hsien-Feng; Lin, Cheng-Li; Lin, Cheng-Chieh; Liao, Kuan-Fu
Abstract : Abstract: Little is known on the relationship between herpes zoster and Parkinson's disease in older people. This study aimed to explore whether herpes zoster could be associated with Parkinson's disease in older people in Taiwan. We conducted a retrospective cohort study using the claim data of the Taiwan National Health Insurance Program. There were 10, 296 subjects aged 65 years and older with newly diagnosed herpes zoster as the herpes zoster group and 39, 405 randomly selected subjects aged 65 years and older without a diagnosis of herpes zoster as the nonherpes zoster group from 1998 to 2010. Both groups were followed up until subjects received a diagnosis of Parkinson's disease. This follow-up design would explore whether subjects with herpes zoster were at an increased risk of Parkinson's disease. Relative risks were estimated by adjusted hazard ratio (HR) and 95% confidence interval (CI) using the multivariable Cox proportional hazards regression model. The incidence of Parkinson's disease was higher in the herpes zoster group than that in the nonherpes zoster group (4.86 vs 4.00 per 1000 person-years, 95% CI 1.14, 1.29). After adjustment for confounding factors, the multivariable Cox proportional hazards regression model revealed that the adjusted HR of Parkinson's disease was 1.17 for the herpes zoster group (95% CI 1.10, 1.25), compared with the nonherpes zoster group. Older people with herpes zoster confer a slightly increased hazard of developing Parkinson's disease when compared to those without herpes zoster. We think that herpes zoster correlates with increased risk of Parkinson's disease in older people. When older people with herpes zoster seek help, clinicians should pay more attention to the development of the cardinal symptoms of Parkinson's disease.